Loss-of-function variants of SCN8A in intellectual disability without seizures. (August 2017) - Wagnon, Jacy L.; Barker, Bryan S.; Ottolini, Matteo; Park, Young; Volkheimer, Alicia; Valdez, Purnima; Swinkels, Marielle E.M.; Patel, Manoj K.; Meisler, Miriam H.
Abstract : Objective: To determine the functional effect of SCN8A missense mutations in 2 children with intellectual disability and developmental delay but no seizures. Methods: Genomic DNA was analyzed by next-generation sequencing. SCN8A variants were introduced into the Nav 1.6 complementary DNA by site-directed mutagenesis. Channel activity was measured electrophysiologically in transfected ND7/23 cells. The stability of the mutant channels was assessed by Western blot. Results: Both children were heterozygous for novel missense variants that altered conserved residues in transmembrane segments of Nav 1.6, p.Gly964Arg in D2S6 and p.Glu1218Lys in D3S1. Both altered amino acids are evolutionarily conserved in vertebrate and invertebrate channels and are predicted to be deleterious. Neither was observed in the general population. Both variants completely prevented the generation of sodium currents in transfected cells. The abundance of Nav 1.6 protein was reduced by the Glu1218Lys substitution. Conclusions: Haploinsufficiency of SCN8A is associated with cognitive impairment. These observations extend the phenotypic spectrum of SCN8A mutations beyond their established role in epileptic encephalopathy (OMIM#614558) and other seizure disorders. SCN8A should be considered as a candidate gene for intellectual disability, regardless of seizure status.